Zimbabwe : Recent Economic Developments, Selected Issues, and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2001)
The combination of wavering domestic policies, governance problems, and costly deployment of troops to support the Democratic Republic of Congo government has seriously affected economic performance and investor confidence. Exchange rate policy continues to be a key issue in Zimbabwe. This paper conducted an empirical analysis of the determinants of the equilibrium real exchange rate (ERER) for Zimbabwe. The results show that the overvaluation in Zimbabwe is sensitive to lax fiscal policy, suggesting that devaluation needs to be underpinned by a tightening of fiscal policy.